Testing the Limits of Optimizing Dual-Task Performance in Younger and Older Adults - Strobach, Tilo; Frensch, Peter; Mueller, Hermann J.; Schubert, Torsten (Frontiers in Human Neuroscience, 2012)
Impaired dual-task performance in younger and older adults can be improved with practice. Optimal conditions even allow for a (near) elimination of this impairment in younger adults. However, it is unknown whether such (near) elimination is the limit of performance improvements in older adults. The present study tests this limit in older adults under conditions of (A) an extremely high amount of dual-task practice and (B) practice with extremely simple component tasks in dual-task situations. The data showed that an extremely high amount of dual-task practice in older adults provided no evidence for an improvement of dual-task performance in older compared with younger adults. However, practice with extremely simple component tasks in dual-task situations during older adults’ practice provided a similar level of improved dual-task performance in both age groups. Thus, applying a testing-the-limits approach, we demonstrated that older adults improve dual-task performance to the same level as younger adults under very specific conditions.